1978
DOI: 10.1002/chin.197818084
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: THERMODYNAMICS OF THE POLYCYCLOTRIMERIZATION OF AROMATIC DICYANATES AND DIISOCYANATES

Abstract: Untersucht wurde die Thermodynamik der Polycyclotrimetisation von 2,2‐Bis‐ (4‐cyanatophenyl)‐propan (I) und 4,4′‐Diphenylmethan‐diisocyanat (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The enthalpy of formation in the liquid state for the former species is 88.3 ± 0.8 kJ/mol [37], and for the later species it has been reported as − 33.9 ± 1.3 kJ/mol [37], while other authors reported the values, respectively of − 61.1 ± 1.1 kJ/mol [8] and of − 55 kJ/mol [38]. Two values for the gas phase enthalpy of formation are reported in the NIST Data Base [13], respectively, − 14.5 ± 1.2 kJ/mol [8] and − 22.1 kJ/mol [32], with reference [8] giving explicitly the value 46.5 ± 0.3 kJ mol −1 for the enthalpy of vaporization of phenyl isocyanate.…”
Section: Comparison With Other Resultsmentioning
confidence: 99%
“…The enthalpy of formation in the liquid state for the former species is 88.3 ± 0.8 kJ/mol [37], and for the later species it has been reported as − 33.9 ± 1.3 kJ/mol [37], while other authors reported the values, respectively of − 61.1 ± 1.1 kJ/mol [8] and of − 55 kJ/mol [38]. Two values for the gas phase enthalpy of formation are reported in the NIST Data Base [13], respectively, − 14.5 ± 1.2 kJ/mol [8] and − 22.1 kJ/mol [32], with reference [8] giving explicitly the value 46.5 ± 0.3 kJ mol −1 for the enthalpy of vaporization of phenyl isocyanate.…”
Section: Comparison With Other Resultsmentioning
confidence: 99%
“…We note there is no example in which there are experimentally measured enthalpy of formation data for an isocyanate, cyanate, and fulminate (nitrile oxide) on the same central atom or group from the experimental literature. The case of phenyl comes close where there are data for the isocyanate [158,159], the cyanate [160], and the 2,4,6-trimethyl derivative of the nitrile oxide [161,162]. We also note the theoretical thermochemical study of the phenyl species as well as their sulfur-containing analogs [163].…”
Section: Issuementioning
confidence: 92%
“…The enthalpy of formation of Mes-CNO is well established [189], but that of its phenyl counterpart is unknown. The enthalpy of formation of MesOCN is unknown, and that of its phenyl counterpart is known only as the liquid [190]. The enthalpy of formation of MesNCO is unknown, but that of its phenyl counterpart has been reported multiple times, the most recent of which [191] differs from an earlier value [192] by approximately 50 kJ mol -1 .…”
Section: Issuementioning
confidence: 99%